Program Edukasi Kesehatan dan Senam Lansia Untuk Penguatan Kemandirian Kelompok Dewasa dan Lansia di Posyandu Terintegrasi Wilayah Kerja Puskesmas Pauh - Tuty Ernawati; Mia Fitria; Farel Benito; Fadya Desril (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Cluster 3 of the Primary Care Integration framework plays a critical role in strengthening community capacity through health education and preventive interventions. This study aimed to improve the knowledge of adult health cadres as well as the physical fitness and independence of older adults at the Pauh Public Health Center. A pre–post intervention study without a control group was conducted involving 25 adult cadres and 15 older adults. Assessment instruments included a structured knowledge questionnaire covering three domains healthy lifestyle and chronic disease prevention, the role of cadres within Primary Care Integration, and communication techniques as well as measurements of physical activity and functional independence among older adults. The intervention consisted of health education for adult cadres, training in elderly assistance and communication techniques, and the implementation of structured exercise sessions accompanied by routine health monitoring for older adults. Results demonstrated substantial improvement in cadre knowledge, with an overall increase of 43.0%, including increases in healthy lifestyle knowledge (39.0%), understanding of cadre roles in Primary Care Integration (44.8%), and communication techniques (45.3%). Among older adults, weekly exercise participation increased from 46.7% to 86.7%, balance ability improved from 8.2 seconds to 13.5 seconds (a 64.6% increase), and daily functional independence rose by 30.0%, resulting in an overall improvement of 44.9%. In conclusion, the Primary Care Integration based health education and elderly exercise program effectively enhanced the capacity of adult cadres and improved the physical fitness and independence of older adults.